The Impacts of Indonesia and Russia Trade Relations on Indonesiaâ€™s Maritime Security (Journal of International Studies, 2016)
This article is to examine the increasing development of the bilateral trade relations between the Republic of Indonesia and the Russian Federation. Also it aims at studying the Indonesia-Russia trade relations on Indonesiaâ€™s national security. Thus, in pursuit of its national interest, Indonesia is working very hard to further strengthen its bilateral trade relations with Russia. Marking the 50 year old relationship in the beginning of the 21st century, the two countries have booked an increasing trade in their relations. This research employed qualitative research methods featuring descriptive analysis of the data on the bilateral relations within â€œThe Framework of Friendly and Partnership in the 21st centuryâ€. Therefore, the author exposed the works of two main consultation mechanisms, namely the Indonesian-Russian Joint Commission on Trade, Economic and Technical Cooperation and the Joint Commission on Military Technical Cooperation under the President Megawati Sukarnoputri administration (2003 - 2004), succeeded by the 1st team of President Susilo Bambang Yudhoyono (2004 -2009) and the 2nd team of President Susilo Bambang Yudhoyono (2009-2014), and President Joko Widodo (2014 - present). An increase is recorded in the overall trade relations of the two countries. Nevertheless, Indonesia still suffered from trade deficit. In addition, the Indonesian defense capability has increased.